Effect of Fenugreek Use on Fasting Blood Glucose, Glycosylated Hemoglobin, Body Mass Index, Waist Circumference, Blood Pressure and Quality of Life in Patients with Type 2 Diabetes Mellitus: A Randomized, Double-Blinded, Placebo-Controlled Clinical Trials: - Gholami-Fesharaki, Mohammad; Hassani, Seyyedeh Seddigheh; Arezodar, Faramarz Fallahi; Esmaeili, Seyyed Saeid (Galen Medical Journal, 2019)
Background: Diabetes mellitus is a major cause of death globally. It causes multiple problems in various organs and incurs heavy costs for patients and the community health system.The present study was conducted to evaluate the effect of fenugreek intake on fasting blood sugar (FBS), HbA1C, body mass index (BMI), waist circumference, blood pressure and quality of life of type 2 diabetes mellitus (T2DM) patients. Materials and Methods: This randomized, double-blinded clinical trial study was conducted on patients with T2DMin Tehran, Iran in 2018. The treatment group received 5 g of fenugreek powder,and the placebo group received 5 g of wheat flour twice daily for two months before meals. Results: This study was performed on 62 patients (50% male and 50% female). Both groups had similar demographic characteristics. The results showed a significant difference between the mean FBS (P<0.001), HgA1C (P<0.001), BMI (P<0.001), waist circumference (P<0.001), diastolic blood pressure (P=0.005), and quality of life (P=0.015). There was no significant difference in mean systolic blood pressure (P=0.189) between groups. Conclusion: Given the positive effect of fenugreek on FBS, hemoglobin, HbA1C, BMI, waist circumference, blood pressure and quality of life, it can be recommended for controlling blood glucose in diabetic patients. [GMJ.2019;8:e1432]